FTA engages in the United Nations Food Systems Summit, contributes to public consultations of the UN Action Tracks, and proposes game-changing solutions that have been adopted by the UNFSS - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
FTA proposed a set of game-changing solutions, and contributed to public consultations of the UN Action Tracks, to dialogues and to debates in action tracks. This significantly influenced the discussions and results. For instance, a game-changing solution, "Delivering healthier diets and restoring degraded land through tree-based food production", was included in Action Track 3 as part of the Agrobiodiversity Solution Cluster.